1983
DOI: 10.1152/ajprenal.1983.245.2.f159
|View full text |Cite
|
Sign up to set email alerts
|

Renal adaptation to alteration in dietary amino acid intake

Abstract: The nonessential beta-amino acid taurine, which is inert in renal tissue, was used to study the renal adaptation to dietary taurine change. Three isoproteinic diets were employed: HTD--high in taurine, NTD--normal taurine, and LTD--deficient in the taurine precursors cysteine and methionine. When compared with NTD, HTD resulted in an increase in the urinary excretion and fractional excretion of taurine, whereas LTD led to a decrease in urinary excretion and fractional excretion of taurine. In vitro studies dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…The composition of the diet is described in detail elsewhere (3,4,17). Briefly each diet (LTD, HTD, or normal taurine diet (NTD)] is isoproteinic and contains soy protein which contains limited amounts of methionine and cysteine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the diet is described in detail elsewhere (3,4,17). Briefly each diet (LTD, HTD, or normal taurine diet (NTD)] is isoproteinic and contains soy protein which contains limited amounts of methionine and cysteine.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the adaptive response occurs within 72 h after initiation of diet (1 7) and is completely established within 6 days. Animals consuming the LTD, which is limiting in methionine and cysteine are 13 k 2% smaller at the end of the 14 days (3,4,17). No attempts are made to pair-feed these animals since the LTD-fed group actually ingests more food.…”
Section: Methodsmentioning
confidence: 99%
“…There are few pathways for taurine metabolism in humans (7,8,22), and urinary taurine excretion may play an important role in regulating body taurine pools (23)(24)(25)(26). Both group 1 and group 2 patients showed a remarkable degree of renal conservation of taurine; their urinary taurine excretion averaged 16% of normal (Table 4).…”
Section: Plasma Taurine (Pmoles/liler)mentioning
confidence: 99%
“…Thus, the renal adaptive response to changes in sulfur amino acid intake is found in the brush border membrane, but the urinary excretion pattern is only partially adapted. It is possible that delayed emux of taurine across the basolateral surface accounts for this excessive taurinuria, since our previous studies have indicated reduced basallateral efflux in immature rats (4,6,7).Although the adaptive response has been shown to partially exist in terms of urinary excretion and to fully exist at the apical surface in 28-day-old rats, little is known about the response in nursing animals at this membrane surface. Herein we describe the influence of the altered amino acid diets fed to the mothers of nursing rats on the renal handling and brush border accumu-…”
mentioning
confidence: 99%
“…Thus, the renal adaptive response to changes in sulfur amino acid intake is found in the brush border membrane, but the urinary excretion pattern is only partially adapted. It is possible that delayed emux of taurine across the basolateral surface accounts for this excessive taurinuria, since our previous studies have indicated reduced basallateral efflux in immature rats (4,6,7).…”
mentioning
confidence: 99%